Evaluation of Modified Atmosphere Packaged Chicken Breast Meat during Refrigeration Storage - Aaliya Tahseen; Gurunathan, Kandeepan (Journal of Meat Science, 2024)
Modified atmospheric packaging (MAP) is most commonly used nowadays to improve the shelf-life of meat in refrigeration storage. Therefore, this research was undertaken to study the effect of MAP on the quality and shelf-life of chicken breast meat (CBM) under refrigeration storage. This was further compared with aerobic packaging (AP) to find the efficiency of MAP. Three different concentrations were used: 1) MAP-20 (20%O2+30%CO2+50%N2), 2) MAP-10 (10%O2+40%CO2+50%N2), and 3) MAP-0 (0%O2+20%CO2+80%N2). Refrigerated storage of CBM with MAP of 0-20% oxygen significantly (p<0.05) decreased TBARS, deoxymyoglobin, metmyoglobin, L* value, b* value, oxygen, and nitrogen but increased the pH, oxymyoglobin, total meat pigment, a* value, carbon dioxide, nitrogen, standard plate count and sensory attributes when compared to aerobic packaging. It can be concluded that a MAP-CBM had a shelf-life of 12 days and AP-CBM had 6 days under refrigeration storage.